Advanced full-scale laboratory dynamic load testing of a ballasted high-speed railway track. (July 2021) - Feng, Bin; Basarah, Yuamar Imarrazan; Gu, Qiusheng; Duan, Xiang; Bian, Xuecheng; Tutumluer, Erol; Hashash, Youssef M.A.; Huang, Hai
Abstract: Understanding ballast layer dynamic response and long-term behavior under moving train loads is necessary for optimization of railway track performance. This paper discussed an advanced testing effort undertaken in a controlled laboratory environment for the measurement of dynamic load responses via multitude of installed sensors and the development of validated computer models and simulation tools suitable for analyzing full-scale ballasted track under dynamic loading. Constructed in a large rectangular metal frame, the laboratory model consisted of a full-scale track with eight ties, ballast, subballast, and embankment. Three different speeds and axle load configurations were applied sequentially onto the full-scale ballasted track using eight actuators, which realistically captured both slow moving freight and high-speed passenger train loads. Vibration velocities were captured at different locations on ballast surfaces and ties. Dynamic soil stresses were recorded at the bottom of the ballast and subballast layers. Both transient and permanent deformations due to repeated dynamic loads were measured in the track substructure layers and for all eight ties. "SmartRock" advanced sensors were used for the first time to track ballast particle movements under dynamic loading. Further, the test data from the experiments were compared with preliminary Discrete Element Method (DEM) simulations.